The development of interactive learning media to improve music learning outcomes - Hidayati, Yeni Tri; Nurharini, Atip (Jurnal Prima Edukasia, 2026)
Limited use of interactive learning media in elementary schools had contributed to low student engagement and unsatisfactory music learning outcomes, particularly in learning about musical instruments diversity. Therefore, technology-based learning media appropriate to students’ characteristics were required. This study aims to develop and evaluate the feasibility and effectiveness of a musical instruments diversity application to improve students of Grade IV music learning outcomes. This research employed a Research and Development (R&D) method adapted from the Borg and Gall model. The research subjects were Grade IV students at Protomulyo 1 Elementary School, Kendal Regency. Data were collected through interviews, observations, documentation, questionnaires, and tests, then analyzed using descriptive analysis, normality testing, N-gain score, and paired sample t-test. The results showed that the application was very feasible, with media expert validation of 96.8% and material expert validation of 95.3%. The paired sample t-test showed a significant value (2-tailed) of 0.000, and the N-gain score was 0.815, indicating high effectiveness. The study concluded that the developed application was feasible and effective in improving Grade IV students’ music learning outcomes, offering a practical model for integrating technology into elementary music education. The findings imply that the strategic integration of interactive mobile applications can bridge the gap between traditional music curricula and digital-age learners, providing a scalable framework for enhancing cultural literacy through technology-driven instruction.